2022
DOI: 10.3390/ijerph19063256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stress and Financials on Romanian Infertile Women Accessing Assisted Reproductive Treatment

Abstract: Around 20% of couples worldwide are affected by infertility issues, with numbers in the European Union reaching as high as 25%, while access to reproductive care varies significantly by geopolitical and country-specific variables. The purpose of this research is to shed light on the unique social, psychological, and financial difficulties faced by Romanian couples seeking access to assisted reproductive therapy (ART). A cross-sectional study was conducted between 2017 and 2019 to involve women who accessed ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Lastly, more researchers observed that individuals with psoriasis who were female had a worse quality of life and were more likely to be stigmatized than patients with the condition who were male [ 28 ]. However, other researchers found that gender did not have a major role in determining quality of life [ 29 ]. In the current research, we found that the amount of stigmatization experienced by male patients was much greater than that experienced by female patients, although the quality of life experienced by female and male patients was almost same.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, more researchers observed that individuals with psoriasis who were female had a worse quality of life and were more likely to be stigmatized than patients with the condition who were male [ 28 ]. However, other researchers found that gender did not have a major role in determining quality of life [ 29 ]. In the current research, we found that the amount of stigmatization experienced by male patients was much greater than that experienced by female patients, although the quality of life experienced by female and male patients was almost same.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the stress faced by women undergoing invasive diagnosis procedures, others experience high levels of stress due to infertility reasons. A vast amount of research has documented the challenges faced by infertile couples and the stress connected with the different phases of the assisted reproductive methods journey, demonstrating the need for counseling [ 38 , 39 ]. These couples manifested high levels of anxiety over the health of their newborns when they faced infertility issues.…”
Section: Discussionmentioning
confidence: 99%
“…If the answers to the question "Does stress affect fertility?" might seem contradictory, according to the previous studies (9)(10)(11)(12), the answer to the question "Does infertility affect stress?" seems significantly more straightforward (13).…”
Section: Infertility and Psychological Distressmentioning
confidence: 97%
“…The link between stress and infertility has generally been studied using a bidirectional approach, i.e., exploring the impact of stress on fertility and the impact of infertility on stress and overall psychological wellbeing. If the answers to the question “ Does stress affect fertility ?” might seem contradictory, according to the previous studies ( 9 12 ), the answer to the question “ Does infertility affect stress? ” seems significantly more straightforward ( 13 ).…”
Section: Introductionmentioning
confidence: 95%